Penerapan Cultural Studies dan Aliran Filsafat dalam Desain Komunikasi Visual - Luzar, Laura Christina; Monica, Monica (Bina Nusantara University, 2014)
Cultural studies is a diversity knowledge from different variety of perspectives, through the production of theory trying to intervene in political culture. Cultural studies explores culture as a practice purport in the context of social force. In this case, cultural studies is not only based on one point only, but also cultural studies tries to compose a variety of theoretical studies of other disciplines developed wider, so that covers a wide range of academic theories that already existed, including Marxism, Structuralism, Post-structuralism, and feminism. By eclectic method, cultural studies puts the positioning to all knowledges, including on its knowledge which integrates with culture, practice of signification, representation, discourse, authority, articulation, text, read, and consumption. Cultural studies could be described as a language game or formation of discourse associated with relation to power in signification practice of human life. In addition to cultural studies, there is also feminism theory participated in the concept of feminist cultural studies that reconstructs and transforms view of misperception between feminism and cultural studies. Feminism affects cultural studies, but not all feminism can be viewed as cultural studies, and not all cultural studies talks about gender. Both of cultural studies and feminism have substantive importance in relation to power, representation, pop-culture, subjectivity, identity and consumption. The theory of social construction is also has connectivity with cultural studies. Construction of reality is inseparable from mark, symbol, and language. Media are full of reality constructed for people to affect people as ethics persuasion in media do.